Definition of Phonetics and Aspects of its Study - Умарова М.С. (Web of Journals Publishing, 2023)
This paper examines stylistically colored phonovariants of words in the Russian and Uzbek languages, which differ in the change of phonemic composition.
Keywords: comparative-typological study, phonetic interference, phonovariants of Russian and Uzbek words, phonetic modification.